Demyelination affects temporal aspects of perception: An optic neuritis study - Raz, Noa; Dotan, Shlomo; Chokron, Sylvie; Ben-Hur, Tamir; Levin, Netta (Annals of neurology, 2012)
Objective: Visual Evoked Potentials (VEPs) following optic neuritis (ON) remain chronically prolonged, although standard visual tests indicate full recovery. We hypothesized that dynamic visual processes, such as motion perception, may be more vulnerable to slowed conduction in the optic nerve, and consequently be better associated with projection rates. Methods: Twenty‐one patients with acute unilateral, first‐ever ON were studied during 1 year. Static visual functions (visual acuity, color perception, visual field, and contrast sensitivity), dynamic visual functions (motion perception), and VEPs were assessed repeatedly. Results: Visual and electrophysiological measurements reached maximal performance 4 months following the acute phase, with no subsequent improvement. Whereas VEP amplitude and static visual functions recovered, VEP latency remained significantly prolonged, and motion perception remained impaired throughout the 12‐month period. A strong correlation was found between VEP latencies and motion perception. Visual performance at 1 month was strongly predictive of visual outcome. For static functions, patients who showed partial recovery at 1 month subsequently achieved full recovery. For dynamic functions, the rate of improvement was constant across patients, independent of the initial deficit level. Interpretation: Conduction velocity in the visual pathways correlated closely with dynamic visual functions, implicating the need for rapid transmission of visual input to perceive motion. Motion perception level may serve as a tool to assess the magnitude of myelination in the visual pathways. The constancy across patients may serve as a baseline to assess the efficacy of currently developing neuroprotective and regenerative therapeutic strategies, targeting myelination in the central nervous system. ANN NEUROL 2012